Entrepreneurship Education and Social Media Usage in Indonesia: Cultivating Entrepreneurial Interest through Entrepreneurial Motivation among Students - Sopi Sopi; Marnoto Marnoto; Wanuri Wanuri; Achmad Junaedi; Masnunah Masnunah (Pinisi Journal of Entrepreneurship Review, 2024)
This study aims to examine the influence of entrepreneurship education, and the use of social media on entrepreneurial interest through entrepreneurial motivation in FEB UNM entrepreneurship students. This type of research is quantitative research. The research design used a survey method with questionnaires as data collection instruments. The study population is all UNM Entrepreneurship Students numbering 427 students. While the sampling technique uses the Proportional Random Sampling technique, which is calculated using from Slovin with a sample result of 84 respondents or 22% of the total population The research method used in this research is quantitative. This research can be a source of information or reference for teaching staff or lecturers in order to be able to direct and guide students related to the development of entrepreneurial interests, Students are also expected to deepen their interest in business management so that they are not focused on the knowledge produced, but also able to conduct business ventures and develop them.